2013
DOI: 10.1186/1742-4755-10-60
|View full text |Cite
|
Sign up to set email alerts
|

National program for family planning and primary health care Pakistan: a SWOT analysis

Abstract: BackgroundThe National Program for Family Planning and Primary Healthcare was launched in 1994. It is one of the largest community based programs in the world, providing primary healthcare services to about 80 million people, most of which is rural poor. The program has been instrumental in improving health related indicators of maternal and child health in the last two decades.MethodsSWOT analysis was used by making recourse to the structure and dynamics of the program as well as searching the literature.SWOT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…It is, therefore, imperative to train community health workers to provide PNC to the women at their homes. In this regard, the lady health workers of Pakistan certainly have the potential to redress the problem [13]. The findings of our study also revealed that the likelihood of receiving PNC in literate women is significantly higher as compare to illiterate women, which again is in concordance with other studies showing that women from communities with higher level of education were more likely to receive PNC [14, 15].…”
Section: Discussionsupporting
confidence: 91%
“…It is, therefore, imperative to train community health workers to provide PNC to the women at their homes. In this regard, the lady health workers of Pakistan certainly have the potential to redress the problem [13]. The findings of our study also revealed that the likelihood of receiving PNC in literate women is significantly higher as compare to illiterate women, which again is in concordance with other studies showing that women from communities with higher level of education were more likely to receive PNC [14, 15].…”
Section: Discussionsupporting
confidence: 91%
“…The declaration emphasised the provision of community oriented preventive, promotive, and curative health services “bringing health care as close as possible to where people live and work.” As such, all countries in the region have endeavoured to create nationwide networks of primary care facilities, and most have ongoing national programmes that focus on primary care 4567…”
Section: Challenges Of Primary Care In South Asiamentioning
confidence: 99%
“…Independent studies including external evaluations of the program shed some light on the factors responsible for this poor outcome. These are poor clinical mentorship and supervisory skills of Lady Health Supervisors (LHS) and dysfunctional supervisory links between LHSs and LHWs [11,[13][14][15][16][17][18]. In order to bridge these supervisory gaps, the Aga Khan University Pakistan in collaboration with health department, government of Sindh introduced an IR project called NIGRAAN.…”
Section: Introductionmentioning
confidence: 99%